Green Synthesis, Characterization and Pharmaceutical Applications of Biocompatible Zinc Oxide Nanoparticles Using Heliotropium rariflorum Stocks - Noor Ul Uza; Ghulam Dastagir; Syed Tanveer Shah; Elitsa Pavlova; Aftab Jamal; Mahmoud F. Seleiman; Jakub Černý (Pharmaceuticals)
Background: Zinc oxide nanoparticles are safe, non-toxic, and biocompatible. These NPs are used in food packaging materials, self-cleaning glass, ceramics, deodorants, sunscreens, paints, coatings, ointments, lotions, and as preservatives. This study explored the biological potential of ZnO nanoparticles synthesized using H. rariflorum. Methods: In vitro antibacterial and antifungal activities against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Candida albicans, Penicillium notatum, Aspergillus flavus, Aspergillus niger and Aspergillus solani were determined. Antioxidant activity was explored using the DPPH radical scavenging method. In vivo analgesic, antipyretic and sedative potential of synthesized nanoparticles was investigated using a mouse model. Results: SEM with various magnification powers showed that some particles were spherical while some were aggregated, flake-shaped, and hexagonal with rough and irregular surfaces. The EDX analysis revealed Zn (12.63%), O (22.83%) and C (63.11%) with trace quantities of Si (0.40%), Ca (0.54%) and P (0.49%). The XRD pattern indicated an amorphous state, with no peaks observed throughout the spectrum. The UV–visible spectrophotometry revealed a characteristic absorption peak at 375 nm, indicating the presence of ZnO nanoparticles. Fourier Transform Infrared Spectroscopy (FTIR) displayed several small peaks between 1793 and 2370 cm−1, providing evidence of the presence of different kinds of organic compounds with different functional groups. ZnO-NPs showed dose-dependent antibacterial and antifungal potential against all strains. Staphylococcus aureus and Candida albicans were the most susceptible strains. The nanoparticles exhibited a maximum antioxidant effect of 85.28% at 100 μg/mL. In this study, the acute toxicity test showed no mortality, and normal behavior was observed in mice at ZnO-NP doses of 5, 10, and 20 mg/kg. For analgesic and antipyretic activities, a two-way ANOVA revealed that dose, time, and the interaction between dose and time were significant. In contrast, the samples had a non-significant effect on sedative activity. Conclusions: This innovative study suggests a potential use of plant resources for managing microbes and treating various diseases, providing a scientific basis for the traditional use of H. rariflorum.